Site fidelity of a migratory species towards its annual range - Lojander, Peter (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2013)
Site fidelity, the behaviour of animals to return to areas where they have been before is a common trait in many species. The Scandinavian moose is known to show fidelity to its range, but to what extent, is little known. The landscape in Sweden changes in a predictable and unpredictable way and hence gives the opportunity to test the existence of fidelity. I used the kernel Brownian bridge method to estimate the home ranges of individual moose over consecutive years and estimated the overlap at the home range level. I also used Euclidian distance to look on calving site fidelity. The moose in Sweden show fidelity to the different parts of their annual range at different levels. The overall pattern is that fidelity towards seasonal range increased with increasing latitude in winter, with a reversed pattern in summer, but the southern populations of moose show high fidelity, all year round. The calving site fidelity also follows the pattern of high fidelity in the south and lower fidelity to the north. This could be explained by the different movement strategies and the predictability of resources vital to the moose across the landscape. The increased knowledge could be used to better manage the Swedish moose population and provide information of the causes of fidelity.